Analysis of optical coherence multiplexing networks for satellite communication. - Kats, G. (IEEE Transactions on wireless communications)
Free-space optical communication between satellites networked together can enable a high data rate between the satellites. Coherence multiplexing (CM) is an attractive technique for satellite networking due to its ability to cope with the asynchronous nature of communication traffic and the dynamic changes taking place in the satellite constellation. The use of optical radiation for intersatellite links creates very narrow beam divergence angles. Due to the narrow beam divergence angle, the vibration of the pointing system, the movement of the satellite, and the large distance between them the pointing from one satellite to another is a complicated task. The vibration of the pointing system is caused by two stochastic fundamental mechanisms: 1) tracking noises created by the electrooptic tracker and 2) vibrations created by internal satellite mechanical mechanisms and external environments. We derive mathematical models of signal, noise, the approximate signal-to-noise ratio, and the approximate bit-error rates of optical communication satellite networks as functions of the system's parameters, the number of satellites, and the vibration amplitude for frequency-shift keying coherence multiplexing (FSK-CM). Based on these models, we can calculate the negative impact of both the number of satellites and the optical terminal vibration on the system's performance.